Catalytic Removal of Soot from Diesel Engines Using CeO2, CeO2-CuO2, and CeO2-Al2O3 Nanocomposites. (2015) - Mahofa, Eubert P.; Narsaiah, T. Bala; Chakra, Ch. Shilpa; Kumar, Pramod
Abstract: Nanosized CeO2 -CuO2 (CeCu, 2:1) and CeO2 -Al2 O3 (CeAl, 2:1) were synthesized by co-precipitation from nitrate precursors using ammonia solution (NH4 OH) as the precipitating agent. The catalysts were calcined in air at 500°C for 4 h to evaluate the thermal stability. The techniques including XRD and DLS were used for catalyst characterization. A Thermo gravimetric/Differential Thermal Analyzer (TG/DTA) was used to determine the catalytic efficiency and soot oxidation reactions. Compared with Ce-free sample, Ce-composite increases the redox properties and the amount of surface lattice oxygen species of the catalyst. The Ce-composite samples exhibited excellent soot catalytic combustion performance by decreasing activation energy of soot oxidation.